2018
DOI: 10.1111/jicd.12372
|View full text |Cite
|
Sign up to set email alerts
|

The impact of post‐traumatic stress disorder on dental and gingival status of children during syrian crisis: A preliminary study

Abstract: Aim Most children in war zone countries often experience post‐traumatic stress disorder (PTSD). This turns the war into a health issue of great importance. The aim was to evaluate dental and gingival status of children suffering from PTSD. Methods A case control study, which included 60 children (30 diagnosed with PTSD and 30 healthy controls) between 9 and 14 years, was undertaken. Dental status was assessed using decayed, missing, and filled teeth (DMFT) for permanent and decayed, missing and filled teeth (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 32 publications
(86 reference statements)
0
10
0
2
Order By: Relevance
“…Similarly, 31.8% of refugees in Sweden and 29.5% of Syrian students had anxiety (23,24). Other studies In Syria found that dental and genitival health deteriorated more in patients with PTSD and psychological disorders (39)(40)(41). Moreover, war affected university students (42), and prevented research from being properly conducted due factors including a shortage of resources (43).…”
Section: Outcomes Of the Psychological Burdenmentioning
confidence: 96%
“…Similarly, 31.8% of refugees in Sweden and 29.5% of Syrian students had anxiety (23,24). Other studies In Syria found that dental and genitival health deteriorated more in patients with PTSD and psychological disorders (39)(40)(41). Moreover, war affected university students (42), and prevented research from being properly conducted due factors including a shortage of resources (43).…”
Section: Outcomes Of the Psychological Burdenmentioning
confidence: 96%
“…Health status is the most frequently researched theme, examined in 38 research papers covering nutrition [ 10 , 94 ], communicable diseases and/or vaccination status [ 8 , 18 , 23 , 26 , 28 , 30 , 38 , 41 , 47 , 54 , 61 , 88 , 94 , 95 ], mental health [ 20 , 27 , 39 , 55 , 56 , 60 , 79 , 83 , 91 , 94 ], child [ 22 , 41 , 57 , 92 ] and maternal [ 93 ] health, oral health [ 44 , 72 , 75 , 83 ], gender-based violence [ 76 ], anaemia [ 43 ] and non-communicable diseases [ 39 , 84 , 94 ]. Of studies examining injuries, three are studies of hospital patients [ 29 , 46 , 89 ], one examines injury burden among children surveyed at home and in camps for internally displaced persons (IDPs) [ 41 ] and one reports injury counts among children and the general population as provided by key informants [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, 31.8% of refugees in Sweden, and 29.5% of Syrian students had anxiety (28,29). Other studies in Syria found that dental and genitival health were associated with PTSD and mental disorders (44)(45)(46). Another study found that around 50% of the population had allergic rhinitis which could be from the direct or indirect effects of war or the unique environment (47).…”
Section: Outcomes Of the Psychological Burdenmentioning
confidence: 95%